UJI ORGANOLEPTIK DAN KIMIA SELAI BERBAHAN DASAR KULIT PISANG TONGKAT LANGIT (Musa troglodytarum L.) - Sangur, Kristin (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2020)
Background: Tongkat langit banana (Musa troglodytarum L.) is popular among the people of Maluku. Tongkat langit banana fruit is used as food and for the treatment of several types of diseases, while the peel is not used, even though the peel contains nutrients that are very important for the body such as carbohydrates, vitamins and minerals. Tongkat langit banana peels can be innovated into jam with the addition of sugar. To find out the sugar concentration that is suitable for the good quality of tongkat langit banana peel jam, it is necessary to carry out an organoleptic test. Apart from organoleptic testing, a chemical test was also carried out on jams. Methods: This research was conducted from January to February 2020. Organoleptic tests were carriedout on 20 semi-trained panelists and then a proximate t analysis was carried out following the SNI 3746: 2008 method. The research data were analyzed descriptively using graphic presentation. Rsults: The parameters assessed in the organoleptic test on jam made from tongkat langit banana peels were color, texture, taste, aroma and level of preference. Apart from organoleptic testing, chemical tests were also carried out on banana peel jams, which included testing for moisture, ash content, fat content, protein content and carbohydrate content. Conclusion: The organoleptic test shows that the higher the sugar concentration in the jam, the lower the color quality of the jam, the more the sweetness of the jam, the more the thickness of the jam increases the distinctive aroma of jam, then the jam that is very popular with panelists is jam with sugar concentration. 50%. The chemical test results showed that the jam with a sugar concentration of 50% contained 25.97% water content, 0.86% ash content, 30.99% carbohydrate content, 0.30% fat content, and 0.13% protein content.